Christian Humanistic Values in the National Educational Thought (Second pt. 19th – the Beginning of the 20th Century) - Oksana Samoilenko (Pedagogical Discourse, 2013)
This article  presents the results of the  analysis of the problems of historiography of Christian humanistic values ​​in the national educational thought in the second part of the  XIX th – the beginning of the XXth century. Methodological directions of forming the scientific interest to this problem: historical and pedagogical, philosophical and religious,  psychological and pedagogical are analysed. It is proved that Christian humanistic values were ​​widely investigated as a pedagogical phenomenon.